Analysis the proportional reasoning abilities of senior high school students in solving mathematical problems - Dhuwi Novita Sari; Helti Lygia Mampouw (STKIP PGRI Banjarmasin, 2019)
This research aims to analyze the proportional reasoning abilities of high school students in solving mathematical problems. Subject of this qualitative descriptive research were 3 of tenth grade students of SMA Negeri 2 Salatiga who have high mathematical abilities. The researchers are the main instrument, supported by test instruments and interview guidelines. Data from the test and interview results were analyzed using steps data reduction, data display, and conclusion drawing. The results showed that the three subjects had different proportional reasoning abilities in solving mathematical problems. The proportional reasoning ability of subject S tends to be at level 1 by showing strategies using images and making qualitative comparisons. The proportional reasoning ability of subject F tends to be at level 2 by showing strategies of connecting models through numerical calculations, using composite units, and using quantitative reasoning. The proportional reasoning ability of subject M tends to be at level 3 by showing strategies using formal methods and knowing invariant and covariant relationships. The three subjects showed proportional reasoning ability at level 0 in solving problems that needed additive and multiplicative comparisons by simply describing the change situation in additive view.